Representing the fragmented mind: Reinterpreting a classic radio feature as 'sonic psychology'. (1st April 2013) - Hendy, David
This article explores the intertwining of ideas about radio and popular psychology in broadcasting's formative years by focusing on the case study of one pioneering BBC producer, Lance Sieveking. Using Sieveking's private papers and other archival sources, the article attempts to reconstruct his private and emotional life in order to help us understand more fully the unusual and experimental programmes he made in the late 1920s. A focus on Sieveking shows an early example of radio being used as a medium capable of representing – and exploring – one's 'inner life'. More specifically, in the 1920s, Sieveking's work is an example of radio being used as a means of working through anxieties and neuroses that are a recognized feature of life in Britain in the aftermath of World War I. It argues that when analysing the creative process in radio – which is, after all, what Paddy Scannell has called a 'human-made' thing – we might want to attend more closely to the personal psychology of its producers.